The Situational Leadership Style Analysis of Principals at Urimesing A3 Ambon Christian Elementary School - Herpiana Sinaga; Aminah Bahasoan; Ivonny Y. Rahanra (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
This study aims to analyze the situational leadership style of the principal at urimesing A3 Ambon Christian elementary school. Effective leadership with adaptive and flexible skills is considered as one of the ways that efforts to lead the organization can be done with situational leadership. Underlying the situational leadership of the principal is the intensity of teaching, direction, social support, concern for the preparation and maturity of teachers and education personnel (Mawardi, 2017). Indicators of situational leadership style mentioned in Diwiyani & Sarino's research (2018) are as follows; telling, selling, pascipate and delegate. From the above symptoms, one of the factors that can influence and support the actions of a teacher is the leadership ability of the leader. So the author wants to conduct research on the situational leadership style of the principal at Urimesing Christian Elementary School A3 Ambon. The research subjects were 4 teachers and the principal. In this study there are four indicators: 1.instruction, 2.consultation, 3.participation, 4.delegation. So based on the results of the Leadership Style Survey conducted by the situational leadership style of the principal at the A3 Ambon urimesing Christian elementary school and the indicators were successful.